Information Technology Governance Analysis using COBIT 2019 Framework in Salatiga City Community and Civil Services - Naibaho, Epson Briantama; Cahyono, Ariya Dwika (Journal of Information System and Informatics, 2024)
Information Technology (IT) is an important part of its value both in terms of investment and intangible potential for an organization in its operational life. The use of IT in government sector organizations, in order to provide services to the public, as well as managing government running mechanisms including interactions with citizens is known as E-Government. The essence of e-Government is efficiency, transparency, public participation and responsiveness of government institutions. The Salatiga City Community and Civil Services is one of the Salatiga city government agencies which is engaged in public services in the field of civil data collection, making IT a supporting component of constitutional management in improving the efficiency of work flows and processes in public services. In order to create efficiency and improve performance in the IT sector, good governance is needed, as well as decision making in the IT sector. Therefore, it requires evaluation and recommendations regarding governance and decision making in the IT sector. Based on this research, recommendations for 5 process domains are provided as a reference as an effort to improve the Information Technology Governance of the Salatiga City Community and Civil Services.